Mitigating urban stress through nature-based solutions: Green spaces in relocation decision-making - Tetiana Dovbischuk (Universität Hamburg, Fakultät für Wirtschafts- und Sozialwissenschaften, WiSo-Forschungslabor, 2024)
As urbanization progresses, urban stress has become an increasingly prominent concern, diminishing city residents' well-being and overall quality of life. Responding to these challenges, nature-based solutions involving urban greenery have emerged as potential stress mitigators, providing respite from the demands of urban life. This paper examines the role of urban green spaces as compensatory strategies for common urban stressors, such as traffic noise annoyance at home, home overcrowding, and the negative effects of the COVID-19 pandemic, in city dwellers' decision-making processes for residential relocations. The data for the analysis are drawn from a primary survey in two German cities, Cologne and Hamburg, encompassing 1,846 randomly selected respondents. The findings suggest that, particularly in the initial stages of considering relocation, individuals use urban green spaces to compensate for stressful urban living conditions. These green space compensation strategies may prevent individuals from progressing to subsequent stages of relocation decision-making. Recognizing the importance of urban green spaces in mitigating urban stress not only enhances the wellbeing of city dwellers but also improves understanding of effective strategies for planning resilient cities.
Keywords: 330; urban green; green spaces; cities; residential relocations; well-being; urban stressors; traffic noise; COVID-19; overcrowding